BUSINESS SHIFTING DURING THE OUTBREAK; IMPULSIVE OR CONTRIVED? GENERATION COHORT PERSPECTIVE - Ni Made Dhian Rani Yulianti; Komang Tri Angga Kusuma Wardani; Ni Kadek Winda Yanti (Jurnal Ilmiah Akuntansi & Bisnis, 2022)
Business shifting during the outbreak; impulsive or contrived? Generation cohort perspective. Although the development and adoption of technology in business has long been carried out, there are still many MSME business actors who do not use it optimally, especially those who are engaged in the culinary business. During the outbreak, one by one they shifted their interaction and transaction system from offline to online since the introduction of interaction restrictions. This shifting rose a fundamental question, was it impulsive behavior (emotional planning) or contrived behavior based on rational planning. This study discussed not only the trigger but also compared it among generational cohort (Gen X, Y, and Z). Qualitative research methodology was used in this study with triangulation data technique, one of which was semi-structured interview to 15 MSME actors. The results showed that generational differences significantly affect the different characteristics of business actors, which lead to different ways of adopting technology into their business. With the lack of mastery of technology, Generation X was proven to adopt technology emotionally because of urgency. Meanwhile, generations Y and Z were proven to adopt technology rationally. Generations X and Y adopt technology based on mature technology mastery and precise planning.